Improved Curie temperature, electromechanical properties and thermal stability in ZnO-modified 0.68Pb(Mg1/3Nb2/3)O3-0.32PbTiO3 ceramics with coexisting monoclinic and tetragonal phases. Issue 4 (April 2018) - Zhang, Ji; Wang, Rui-Xue; Sun, Lei; Luo, Zhen-Lin; Chen, Y.B.; Chang, Yun-Fei; Gu, Zheng-Bin; Lu, Ming-Hui; Yang, Bin; Zhang, Shan-Tao
Abstract: Further improving electromechanical properties and overcoming relatively low Curie temperature ( Tc ) of (1- x )Pb(Mg1/3 Nb2/3 )O3 - x PbTiO3 (PMN-100 x PT) are still two scientific issues. Here, we demonstrate a stable coexistence of monoclinic-tetragonal (MC -T) phases in ZnO-modified PMN-32PT (PMN-32PT: x ZnO) due to the diffusion-induced substitution of Zn 2+ for Mg 2+ . The Curie temperature, saturated polarization, remnant polarization, piezoelectric coefficient ( Tc, Ps, Pr, d33 ) are increased from (160 °C, 22.0 μC/cm 2, 13.3 μC/cm 2, 350 pC/N) for x  = 0 to (180 °C, 30.3 μC/cm 2, 22.4 μC/cm 2, 470 pC/N) for x  = 0.06. Moreover, the thermal stability is improved. After annealing at 150 °C, the x  = 0.06 sample shows retrained d33 value of 209 pC/N, about 4 times larger than that of x  = 0 counterpart. The improved properties are attributed to the substituting increased polar nanoregions and easy domain switching in MC phase.